Price and quality in the UK childcare market - Alan Duncan; Gillian Paull; Jayne Taylor (Institute for Fiscal Studies (IFS), 2001)
Childcare subsidies are typically advocated as a means to making paid employment profitable for mothers, but also have important ramifications for the use and quality of paid childcare. Even if one is concerned primarily with the quantity aspect, the quality dimension cannot be ignored. This paper provides an exposition of the potential biases in estimates of price elasticities with respect to quantity that do not allow for quality variation or for the possibility of non-linear pricing structures. Using an approach developed in the demand estimation literature, a price measure addressing these issues is derived and the importance of using this measure is tested using British data. Price is found to have a negative impact on the use of formal paid care, the hours purchased and the quality chosen. However, failure to control for quality effects and non-linearities in the price measure is shown to generate significant overestimates of the price elasticities.
Keywords: D12; J13; 330; childcare; unit values; quality; Kinderbetreuung; Dienstleistungsqualität; Großbritannien